The Unity of Knowledge in the Perspective of Syed Muhammad Naquib al-Attas: An Epistemological Analysis of Islamic Education - Maidatus Sholihah; Sunanto; Moch. Anang Afifuddin; Mohamad Salik (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Contemporary Islamic education faces serious challenges due to the penetration of Western worldviews that have triggered secularization, fragmentation of knowledge, and degradation of manners in educational practices. This condition shows that the crisis in Islamic education is epistemological, not merely technical or curricular. This study aims to analyze Syed Muhammad Naquib al-Attas’s thoughts on the unity of knowledge in Islam by grounding epistemology in manners. This research uses a literature review method with a historical-philosophical approach, analyzing al-Attas’s major works and relevant secondary literature published in the last 10 years. The results of the study show that al-Attas interprets adab not merely as behavioral ethics but as an epistemological structure that organizes the relationship between the subject, the object, and the purpose of knowledge, while restoring the relationship between revelation and reason in education. His concept of the unity of knowledge is based on tawhid as an ontological and epistemological principle, thus rejecting the dichotomy between religious and secular knowledge. These findings confirm that al-Attas’ epistemology is applicable and relevant to the development of an integrative curriculum and value-based learning at the MI/SD level, particularly in the context of the Merdeka Curriculum.